Training on Interpreting Featured Products for UMKM Actors in Using English in Cireundeu - indrianty, septy; Agoes, Adrian (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
This training is designed to empower UMKM actors and local residents in Cireundeu Traditional Village through English, focused on marketing featured cassava-based products. The objectives of this training are: (1) to increase the public's confidence in using English, (2) to develop their storytelling abilities in English to describe "Rasi" and other cassava-based products, and (3) to raise awareness of the importance of product interpretation as a marketing tool. The method used is presenting the interpretation material in English. As for the stages in carrying out the training activities, they begin with a post-test questionnaire before the training, followed by material presentation and Q&A, presentation practice on making “rasi” in English, and finally a post-test after the training. The overall results of this training show that it has provided a very significant improvement. The largest percentage increase was in the participants' ability to tell stories about 'Rasi' in English. Based on average analysis, the training had a positive impact in all measured areas. The most dramatic improvement was seen in practical English language skills, particularly in their ability to describe their products, which is a key skill for interacting with tourists. One way to optimize training is to conduct intensive training and provide continuous support.